2020
DOI: 10.1017/s0022029920000916
|View full text |Cite
|
Sign up to set email alerts
|

Natural tree shade increases milk stability of lactating dairy cows during the summer in the subtropics

Abstract: This research communication addresses the hypothesis that, during the summer in the subtropics, natural tree shade helps to improve milk functional characteristics such as stability and acidity. Sixteen Holstein lactating cows were enrolled. The study consisted of three periods (pre-stress, heat stress and post-stress) based on allocating grazing cows into two treatments (with and without access to shade during the Heat Stress period). Overall THI during the trial was (mean ± se) 76.0 ± 3.4. Access to shade pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Titratable acidity differed among groups but stayed inside the preconized range (14 to 18ºD) and in the same ascending tendency observed before starting the experiment: H100<H75<H50. In Abreu et al (2020), cows under stress and without shade showed a loss of stability associated with higher titratable acidity. Holstein cattle (H100) are more heat susceptible.…”
Section: Discussionmentioning
confidence: 97%
“…Titratable acidity differed among groups but stayed inside the preconized range (14 to 18ºD) and in the same ascending tendency observed before starting the experiment: H100<H75<H50. In Abreu et al (2020), cows under stress and without shade showed a loss of stability associated with higher titratable acidity. Holstein cattle (H100) are more heat susceptible.…”
Section: Discussionmentioning
confidence: 97%
“…However, only 27-39% of the variations in milk yield, acidity, protein and lactose concentrations are explained by feed restriction. Authors acknowledge the multifactorial nature of milk stability, reflecting variations in mineral composition (Tsioulpas et al, 2007), acidity and caseins affected by feeding practices (Gabbi et al, 2015(Gabbi et al, , 2018 as well as animal health, breed (Vizzotto et al, 2021), metabolic status (Marques et al, 2011), lactation stage (Marques et al, 2010a) and heat stress (Abreu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors affect milk stability, including nutrition (Stumpf et al ., 2013), feeding (Pinheiro et al ., 2022), genetics (Davis et al ., 2001), age or number of lactations, lactation stage (Omoarukhe et al ., 2010), environmental factors, mammary gland health including bacterial contamination (Zanela et al ., 2006), methodological factors (Zanela and Ribeiro, 2018), heat stress (Abreu et al ., 2020) and the concentration of ionized calcium (iCa) in milk (Akkerman et al ., 2019). These factors have already been identified and associated with cases of low milk stability on small farms, however, few studies have evaluated the effect of these factors on milk stability in herds with different levels of technical management.…”
mentioning
confidence: 99%